Vaccinating Adolescents With Intellectual and Developmental Disability at School: An Opportunity to Promote Supported Decision Making. - Klinner, Christiane; Young, Alexandra; Strnadová, Iva; O'Neill, Jenny; Newman, Christy E.; Wong, Horas; Davies, Cristyn; Vujovich-Dunn, Cassandra; Skinner, S. Rachel; Brogan, Deidre; Kang, Melissa; Danchin, Margie; et al. (Journal of School Nursing, 2026)
Internationally, vaccination rates among adolescents with intellectual and developmental disability (IDD) are lower than those of the general population. Little research has addressed this issue. This study investigates the experiences of vaccinating adolescents with IDD in special education settings in Australia, with a focus on student engagement. Semistructured interviews and focus groups were undertaken with 50 stakeholders involved in the school vaccination program. Data was analyzed thematically using a framework approach. We identified five themes: lack of student engagement, practices discouraging engagement, practices fostering engagement, lack of vaccination protocol adjustments, and lack of disability-specific nurse training. Nurses' limited knowledge and skills in engaging students with IDD can result in unethical practices, students feeling excluded from vaccination decisions, and students being traumatized by negative treatment experiences. Clinical protocols lack guidance and reasonable adjustments to provide inclusive vaccination services. Supported decision making could provide more inclusive school vaccinations, more positive vaccination experiences, and higher vaccination rates among adolescents with IDD.